Antihyperglycemic activity of Caralluma quadrangula in streptozotocin-induced diabetic rats - Essam Abdel-Sattar; Shohda A. EL-Maraghy; Riham Salah El-Dine; Sherine M. Rizk (Faculty of Pharmacy, Cairo University, 2017)
Diabetes of type 2 is a worldwide epidemic disease of global prevalence. Caralluma quadrangula is wild Saudi plant used by traditional healers as antidiabetic, in case of hunger, and many other diseases. Nothing was reported to justify the use of the plant in case of diabetes. The plant material was extracted with water and with methanol, the methanol fraction was further fractionated into chloroform, n-butanol, in addition to the remaining mother liquor. The water and methanolic extracts as well as different methanolic fractions were evaluated in STZ-induced diabetic rats for their antihyperglycaemic activity. The results showed a significant decrease in fasting blood glucose levels in diabetic treated rats after the administration of most of the extracts and fractions of C. quadrangula and glibenclamide. The most potent activity was shown by administration of the methanolic extract (200 mg/kg), chloroform, n-butanol fraction at dose of 100 mg/kg, as well as the major pregnane glycoside russelioside B isolated from C. quadrangula. In conclusion, this study proved the traditional use of C. quadrangula in diabetes mellitus. Keywords: Asclepiadaceae, Caralluma quadrangula, Antihyperglycemic, Fast blood glucose, G-6-Pase, Insulin